The Effect of Addition of Sodium Lactate in Fish Balls made from Fresh Rainbow Trout (Oncorhynchus mykiss W.) - Oksuztepe, Gulsum; Coban, Ozlem Emir; Guran, Husnu Sahan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2010)
In this study, microbiological, chemical and sensory changes of fish balls made from rainbow trout (Oncorhynchus mykiss W.) treated with addition of sodium lactate at different percentages [0.5% (group A), 1% (group B) and 2% (group C)] were analyzed during their storage. Total mesophilic aerobic bacteria count of fish balls was determined 4.11 log(10) cfu/g on day 0. The count relatively decreased until day 2 and then constantly increased in all groups during the remaining storage. Statistical analyses showed that treatment with sodium lactate was effective on total mesophilic aerobic bacteria count of fish balls (P<0.05). The numbers of coliform, Staphylococcus - Micrococcus and yeast and mould increased in all groups as from beginning of the storage. Numbers of Staphylococcus - Micrococcus and yeast and mould in group C was found to be lower from other groups (P<0.05). It was not seen significant difference between groups in terms of pH, dry matter, ash and salt levels (P>0.05). TVB-N and TBA values gradually increased in all groups during the storage period. Significant differences was found between groups in point of TVB-N and TBA values (P<0.05). Although fish balls were found to be desirable from sensorial point of view at the beginning of the storage, their sensory attributes gradually decreased during the storage period (P<0.05). It was seen that addition of sodium lactate at 2% to fish balls increased the shelf life of the product while it did not have negative effect on sensory attributes of the product. In conclusion, it was observed that fish balls with addition of 2% sodium lactate were found to be acceptable up to 16 days at +4 +/- 1 degrees C.
Sodyum laktat İlavesinin taze gökkuşa?ialabali?indan (Oncorhynchus mykiss W.) Yapilan Köftelere etkisi
Keywords: Sodium lactate; Rainbow trout; Meat balls; Microbiology quality; Chemical quality